Evaluasi Kinerja Penerapan Green Road Construction pada Proyek Jalan Tol KKT Kariangau – Sp. Tempadung (Tol IKN 3B) dengan Metode Importance Performance Analysis (IPA) - Nuril Huda; Henri Siswanto; Dwi Siswahyudi (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2026)
Nusantara Capital City (IKN), designated as Indonesia’s new capital under Law Number 3 of 2022, is envisioned as a sustainable, eco-friendly forest city; consequently, strategic infrastructure such as the KKT Kariangau–Sp. Tempadung Toll Road (IKN Toll 3B) must strictly comply with green standards, yet empirical evaluation of its actual on-site construction performance remains highly limited. Implementing Green Road Construction is vital to reducing environmental impacts and strengthening sustainability commitments. This study evaluates its performance using the Importance Performance Analysis (IPA) method, based on responses from 42 participants comprising service users, providers, and supervising consultants. Results show an average importance score of 4.42 and a performance score of 4.17. Most indicators fall into Quadrant II (Maintain Performance), while energy-efficient lighting and excess material use fall into Quadrant I (Top Priority). Indicators related to energy, water, and materials are in Quadrant III (Low Priority), and none are in Quadrant IV. Overall, the implementation is satisfactory, with recommendations to enhance energy efficiency and material management to support sustainable toll road development in IKN further Keywords: Green Road Construction; Toll Road; Importance Performance Analysis (IPA); Sustainability; Nusantara Capital City (IKN).